2018
DOI: 10.3390/ijms19041028
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analyses of the NAC Transcription Factor Gene Family in Pepper (Capsicum annuum L.): Chromosome Location, Phylogeny, Structure, Expression Patterns, Cis-Elements in the Promoter, and Interaction Network

Abstract: The NAM, ATAF1/2, and CUC2 (NAC) transcription factors form a large plant-specific gene family, which is involved in the regulation of tissue development in response to biotic and abiotic stress. To date, there have been no comprehensive studies investigating chromosomal location, gene structure, gene phylogeny, conserved motifs, or gene expression of NAC in pepper (Capsicum annuum L.). The recent release of the complete genome sequence of pepper allowed us to perform a genome-wide investigation of Capsicum an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 46 publications
3
49
0
Order By: Relevance
“…A total of 180 NAC genes were identified in broomcorn millet. The number of NAC genes in broomcorn millet was higher than the 117 in A. thaliana [41], 151 in rice [60], 104 in pepper [51], 82 in melon [53], 96 in cassava [53], 152 in maize [45], 147 in foxtail millet [47], 152 in soybean [48], and 110 in potato [49], and lower than that of 288 in bread wheat [42] and 188 in Chinese cabbage [50]. There were extensive variations in gene length, predicted protein MW, and protein pI, whereas the gene structures and protein motifs were relatively conserved in the clades, which provided a valuable reference for their analysis and function.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…A total of 180 NAC genes were identified in broomcorn millet. The number of NAC genes in broomcorn millet was higher than the 117 in A. thaliana [41], 151 in rice [60], 104 in pepper [51], 82 in melon [53], 96 in cassava [53], 152 in maize [45], 147 in foxtail millet [47], 152 in soybean [48], and 110 in potato [49], and lower than that of 288 in bread wheat [42] and 188 in Chinese cabbage [50]. There were extensive variations in gene length, predicted protein MW, and protein pI, whereas the gene structures and protein motifs were relatively conserved in the clades, which provided a valuable reference for their analysis and function.…”
Section: Discussionmentioning
confidence: 85%
“…All 180 PmNAC members were divided into 12 subgroups based on their sequence homology and classification from Arabidopsis [41]. Phylogenetic analysis divided tartary buckwheat, cassava and pepper NACs into 15, 16 and 14 subgroups, respectively [44,45,51]. These data indicated that NAC proteins showed diversity in different species.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Consequently, non-synonymous (Ka) and synonymous substitution (Ks) among duplicated CaRLK gene pairs were calculated using PAL2NAL (http://www.bork.embl.de/pal2nal/). The divergence time of the duplicated gene pairs was calculated as described by Koch et al (2000) [21].…”
Section: Methodsmentioning
confidence: 99%
“…The genome wide analyses of each transcription factor have been completed and "-"indicates the genome wide analysis was not done yet. Potato's WRKY [63] Dof [58], NAC [145]; ARF [192]; ERF [181] Pepper WRKY [193] ERF [194]; Dof [51] MYB [103]; ARF [190]; NAC [195] Tomato WRKY [62] Dof [53] MYB [88] HSF [120] ARF [196] ERF [171]; Eggplant's WRKY [197] Dof [52] MYB [84].…”
Section: List Of Major Transcription Factors In Major Solanaceous Foomentioning
confidence: 99%